Brazilian marine biogeography: a multi-taxa approach for outlining sectorization - Cord, Isadora; Nunes, Lucas T.; Barroso, Cristiane X.; Freire, Andrea S.; Gadig, Otto B. F. [UNESP]; Gomes, Paula B.; Gurgel, Carlos F. D.; Lindner, Alberto; Mantelatto, Fernando L.; Targino, Alessandra K. G.; Floeter, Sergio R. (Springer Nature, 2022)
Species distribution patterns in the Brazilian Marine Province (BMP) are extensively debated, nevertheless no study used a multi-taxa approach to investigate possible biotic distinctions and the role of environmental factors in determining biogeographical patterns in this province. Here, we compiled the largest distributional multi-taxa dataset in the southern Atlantic (2412 reef species) to address the following: (1) similarities among areas accounting for species composition and environmental characteristics; (2) the absolute species richness of nine taxonomic groups among geographical bins; and (3) how species biogeographical patterns are explained by the environmental similarities. We hypothesized sub-provinces’ limits will be strongly correlated to environmental delimitations, being sea surface temperature a central component influencing biotic subdivision on the BMP. We found eight different geographical bins considering the environmental factors, while five considering species distributions. We also observed a latitudinal gradient of species richness for most taxa, some presenting a “mid-domain” shape pattern. Beta diversity among sub-provinces was low, and the nestedness component more important, indicating high connectivity along the BMP. Using a db-RDA, we demonstrated that environmental variables explained 64% of species clustering patterns, with sea surface temperature, water turbidity and current velocity explaining the biotic clustering of the Brazilian northeastern coast. Sub-provinces North and Abrolhos Bank were the most distinct areas regarding environmental and biotic data. Our study highlights the importance of using a multi-taxa approach to understand the relationship between biogeographical patterns, as well as its response to environmental and historical factors.
Keywords: Ecological filters; Latitudinal gradients; Marine biogeography; Reef environments; Species distributions